2022
DOI: 10.1136/gutjnl-2021-326500
|View full text |Cite
|
Sign up to set email alerts
|

Protective and aggressive bacterial subsets and metabolites modify hepatobiliary inflammation and fibrosis in a murine model of PSC

Abstract: ObjectiveConflicting microbiota data exist for primary sclerosing cholangitis (PSC) and experimental models. Goal: define the function of complex resident microbes and their association relevant to PSC patients by studying germ-free (GF) and antibiotic-treated specific pathogen-free (SPF) multidrug-resistant 2 deficient (mdr2−/−) mice and microbial profiles in PSC patient cohorts.DesignWe measured weights, liver enzymes, RNA expression, histological, immunohistochemical and fibrotic biochemical parameters, fae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Importantly, it has been known since the 1970s that GF conditions but also antibiotics increase the bile acid pool size in rodents 9. In this respect, the current findings of Awoniyi et al 6 are therefore in line with previous observations,10 but the rescue of the liver phenotype with Lachnospiraceae and purified SCFAs is new and fascinating! However, we have to consider that it remains an unresolved question whether biliary bile acids play a role in bile duct injury in PSC, since patients with PSC show regular bile composition in this respect 11.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Importantly, it has been known since the 1970s that GF conditions but also antibiotics increase the bile acid pool size in rodents 9. In this respect, the current findings of Awoniyi et al 6 are therefore in line with previous observations,10 but the rescue of the liver phenotype with Lachnospiraceae and purified SCFAs is new and fascinating! However, we have to consider that it remains an unresolved question whether biliary bile acids play a role in bile duct injury in PSC, since patients with PSC show regular bile composition in this respect 11.…”
supporting
confidence: 87%
“…In Gut , Awoniyi et al 6 show that germ-free (GF) conditions cause 100% mortality in Mdr2 (Abcb4) −/− mice and that selective pathogen-free faecal microbiota transplantation rescued mice. In addition, treating the mice with vancomycin exaggerated liver injury in parallel with reduction of Lachnospiraceae and increase of Enterococcus and Enterobacteriaceae abundance, together with increased bacterial translocation, presumably from the gut to the liver, of Enterococcus faecalis and Escherichia coli strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the effects of antibiotics on bile acid homeostasis at the levels investigated in the present study, it was reported that depletion of gut microbiota by antibiotics may result in induction of Cyp7a1 expression in the liver, thereby enhancing bile acid synthesis (Awoniyi et al 2022;Schneider et al 2021). Development of a new approach methodology (NAM) to capture these effects is an interesting topic for future studies.…”
Section: Discussionmentioning
confidence: 89%
“… 49 Studies have demonstrated that short chain fatty acids (SCFAs), have a role in reducing inflammatory immune responses. 51 …”
Section: Discussionmentioning
confidence: 99%